Peranan Teknologi Informasi Dalam Efektivitas Sistem Pengendalian Intern Koperasi Bina Citra Wanita - Majidah, Shinta; Pratiwi, Yana; Lastiani, Siwidyah (JFAS : Journal of Finance and Accounting Studies, 2023)
This study aims to analyze the effect of the use of information technology on the effectiveness of the internal control system in the Bina Citra Women's Cooperative in Menganti Gresik. The research method used is qualitative, involving cooperative heads, cooperative treasurers, and cooperative members as informants. Data collection techniques were carried out through interviews with cooperative members and management, direct observation of activities in cooperatives, and study of documents such as cooperative SOPs, financial reports, and information technology usage policies. The results of the study show that cooperative members have a positive perception of the influence of the use of information technology in increasing the effectiveness of the cooperative's internal control system. Information technology helps in prioritizing customer service, preventing fraud, and reducing the risk of fraud